The Comparison between Preoperative Maltodextrine and Sugar Water Administration on Random Blood Glucose Levels in Enhanced Recovery After Cesarean Surgery (ERACS) Patients - Satrio Adi Wicaksono; Dwi Pudjanarko; Ignatius Riwanto (JAI (Jurnal Anestesiologi Indonesia))
Background: Oral carbohydrate administration reduces post-operative insulin resistance and improves post-operative recovery. Sugar water and maltodextrin are oral carbohydrates that can be given to enhanced recovery after caesarean surgery (ERACS) patients.